PENGARUH P-O FIT DAN LAISSEZ-FAIRE LEADERSHIP ERHADAP KINERJA MELALUI KEPUASAN KERJA DAN OCB (Studi pada Satuan Kerja Perangkat Daerah (SKPD) Pemerintah Kota Semarang) - Hartono, Joko; Priyono, Bambang Suko (Jurnal Ilmiah Telaah Manajemen, 2014)
This study examines the effect of Person-Organization Fit and Laissez-Faire Leadership to Performance through Work Satisfaction and Organizational Citizenship Behavior. This research was conducted on Semarang City Government civil servants. The research instrument used was a questionnaire tested for validity and reliability. It is also to explain the influence of independent variables to dependent variables using multiple linear regression equation. Model and hypothesis test used F test, t test and beta coeffiecient. The result showed that (1) Person-Organization Fit positively influences work satisfaction, (2) Laissez-Faire Leadership positively influences work satisfaction, (3) Person-Organization Fit positively influences Organizational Citizenship Behavior, (4) Laissez-Faire Leadership negatively influences Organizational Citizenship Behavior, (5) Work satisfaction positively influences Organizational Citizenship Behavior, (6) Person-Organization Fit positively influences performance, (7) Laissez-Faire Leadership has no effect on performance, (8) Work Satisfaction positively influences performance and (9) Organizational Citizenship Behavior positively influences performance. Keywords: person-organization fit, laissez-faire leadership, work satisfaction, organizational citizenship behavior, and performance